Está bien no estar bien - Olivas Macassi, Pierinna Nicolle (2020)
Está Bien No Estar Bien (It is ok not to be ok)is a photographic project about depression, in which, through documentary photography, I portray two women aged 25 and 26 with depression, using the social network Instagram as a platform. The purpose of this project is to make depression visible and create a space for the photographed people to tell their experience through written testimonies that accompany the photographs.For this, a research work has been carried out with secondary sources, using bibliographic material, in-depth interviews with people with depression and focus groups with people who have not been diagnosed with depression.In the following chapters, the current situation of depression and mental health in the country, as well as in society in general, will be explained. Furthermore, the creative process of taking the photographs, the final result of the exhibition of the project on the social network Instagram and the learned lessons will be exposed.